Perbandingan Sistem Politik Dan Demokrasi: Studi Kasus Indonesia Dan Filipina Dalam Konteks Sejarah Politik Dan Pemilihan Umum - Harefa, Erwin; Dompak, Timbul; Harefa, Remember To; Salsabila, Lubna (LPPM Universitas Putera Batam, 2024)
Indonesia and the Philippines, both located in Southeast Asia, have a remarkably similar political history. Both nations are governed by authoritarian regimes. During that period, the electoral political system was established and comprehensively governed by all political components. Democracy has ceased to exist and is now closely linked to a political framework that is under the power of the government. The utilization of general elections as a metric can serve as an indication of the caliber of a nation's democratic system. If the elections in that country are conducted smoothly and citizens actively engage, then the country is seen as possessing commendable democratic attributes. This serves as a lesson for Indonesia and the Philippines to enhance the execution of elections and democracy by enacting more effective legislation and establishing a superior electoral system compared to the previous one. The electoral system is subject to constant adaptation based on the specific characteristics of each country, with the aim of establishing a system that is advantageous for the population.